Outcomes of a pilot feasibility study of comprehensive geriatric assessment for younger frail patients with severe mental illness - Urska Arnautovska; Rebecca Soole; Winona Wing Ling Kwan; Natasha Reid; Andrea Baker; Emily H. Gordon; Ruth E. Hubbard; Dan Siskind; Nicola Warren (BMC Psychiatry)
Abstract Background Individuals with severe mental illness (SMI) are at risk of early-onset frailty, leading to adverse outcomes. Effective interventions for reducing frailty in this population are currently lacking. Aims To assess the feasibility, acceptability, and preliminary efficacy of Comprehensive Geriatric Assessment (CGA), delivered by an Advanced Trainee in Geriatric Medicine, as an intervention for individuals with co-occurring frailty and SMI. Method Participants, aged 18–64, with frailty and SMI were recruited from public community outpatient clinics between July 2022 and January 2023. Feasibility of CGA was evaluated through mixed methods. Secondary outcomes included a range of mental and physical health factors. Results Out of 38 eligible individuals, 17 were enrolled and 14 completed the study; three dropped out post-baseline assessment and CGA. 86% were male, average age was 48.4, Body Mass Index 34.6, and Frailty Index 0.35. Participants expressed high acceptability and perceived benefits of CGA, including increased insight about one’s health and receipt of multidisciplinary holistic care. While this study was inadequately powered to show statistically significant changes in secondary outcomes, positive trends were observed in overall psychosis symptoms and weekly physical activity engagement which increased by 56.6 min, reaching the recommended levels to achieve health benefits. Conclusion The findings of this study support the feasibility of CGA as an intervention in routine care of people with SMI and provide evidence for designing future trials of frailty interventions in this population. The study underscores the significance of tailored, multidisciplinary, and individualised approaches, though further research is required to substantiate its efficacy in this priority population.